2021
DOI: 10.1186/s40510-021-00365-5
|View full text |Cite
|
Sign up to set email alerts
|

Mini Hyrax vs Hyrax expanders in the rapid palatal expansion in adolescents with posterior crossbite: a randomized controlled clinical trial

Abstract: Purpose The aim of this study was to compare the dental effects, impact on quality of life, and pain perception of adolescents wearing Mini Hyrax and Hyrax expanders in rapid palatal expansion. Methods Thirty-four adolescents aged 11 to 16 years, with maxillary transverse deficiency (unilateral or bilateral posterior crossbite), were randomly allocated into two groups, Mini Hyrax group and Hyrax group (1:1 ratio). Dental effects were evaluated by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
1
4
0
7
Order By: Relevance
“…Pain was assessed every day in the first week only in the study by Ugolini et al [ 24 ] in which pain was perceived more in both groups especially during the first 4 days. This is in accordance with previous studies in particular during RME treatment [ 27 , 29 , 31 , 32 , 50 ]. In one study [ 35 ], pain was evaluated until 12th week; it decreased quickly after 3rd week, and from the 5th week to the 12th week it was almost nil, around 0.1 on VAS.…”
Section: Discussionsupporting
confidence: 94%
“…Pain was assessed every day in the first week only in the study by Ugolini et al [ 24 ] in which pain was perceived more in both groups especially during the first 4 days. This is in accordance with previous studies in particular during RME treatment [ 27 , 29 , 31 , 32 , 50 ]. In one study [ 35 ], pain was evaluated until 12th week; it decreased quickly after 3rd week, and from the 5th week to the 12th week it was almost nil, around 0.1 on VAS.…”
Section: Discussionsupporting
confidence: 94%
“…The number of activations suggested was almost the same in all designs: in two studies, the screw was turned two times a day, for the first week, then the appliance was activated one time per day; the screw used was a 9 mm Hyrax for the TB group and a 9 mm Jackscrew for the MARPE TTB group [ 23 , 24 ]. In 11 studies suggested activating the screw two times a day until the finish of the expansion: the screws used in these cases were 9 mm Hyrax in the 9 TB group; a Hyrax miniscrew was used in the 1 TB group and 12 mm Hyrax jackscrew in the 1 TB group; one group used the Keles Keyless screw; in the MARPE TTB groups, two studies used 8 mm a miniexpander jackscrew and one study used a 12 mm jackscrew [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Two studies suggested one activation/day with the Hyrax screw [ 36 , 37 ], and the protocol was not determined in one study [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hyrax design appliances are the most commonly used: they present bands on U6 and maxillary first premolars and a 9 mm expansion screw. Mini Hyrax design appliances present only two bands, and the first molars are the anchorage elements; the screw is 8 mm long [ 26 ]. Silveira et al stated that Hyrax and Mini-Hyrax devices are similar in terms of orthodontic and orthopedic effects and patient’s comfort [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otra parte, los huesos maxilares aproximadamente forman el 50% de las estructuras anatómicas de la cavidad nasal, para mejorar la función normal la posición adecuada de la lengua y el patrón de crecimiento fisiológico el tratamiento de una deficiencia transversal se debería llevar a cabo lo antes posible (Santos Silveira et al, 2021). Es por eso que, la constricción maxilar podría reducir el crecimiento transversal y sagital causando una maloclusión clase II, de tal manera, el principal hallazgo clínico de la constricción maxilar son las mordidas cruzadas posteriores unilaterales o bilaterales, la prevalencia de estas mordidas oscila entre el 10% y el 15%, sin emabrgo, esta alteración del maxilar no tiene predilección por sexo o etnia del individuo.…”
Section: Aspectos éTicosunclassified